ARUS TOP-DOWN DAN BOTTOM-UP PADA GERAKAN DIALOG ANTAR AGAMA DI INDONESIA - Muhammad Muhammad; Nurlaila Nurlaila (Abrahamic Religions: Jurnal Studi Agama-Agama, 2021)
The interfaith dialogue movement in the top-down current as described above, namely the movement originating from the state, was welcomed by various communities in Indonesia as a bottom-up current, namely the interfaith dialogue movement originating from the people. At least in this bottom-up flow, there are two communities, namely dialogue developed in academic institutions, and dialogue conducted or facilitated by civil society institutions, such as NGOs (Non-Governmental Organizations), both focusing on dialogue and raising issues. -Other issues related to dialogue. In this research, the researcher focuses only on two groups, namely the state (top-down current) and academic institutions (bottom-up current) trying to examine religious movements in the realm of inter-religious dialogue using social movement theory. There are three key concepts in social movement theory which usually play a very important role in determining the success of collective action. The three concepts include (1) political opportunity structure, (2) mobilizing structures, and (3) framing of action.